(untitled) (Indian Journal of Child Health, 2020)
Rhizobium radiobacter is an opportunistic human pathogen. Infections due to R. radiobacter are strongly related to the presence of foreign plastic materials and effective treatment often requires removal of the device. We report a case of R. radiobacter bloodstream infection associated with a central venous catheter, which was easily controlled by antimicrobial treatment and removal of the catheter. To the best of our knowledge, this is the first case report of R. radiobacter as a cause of central line-associated bloodstream infection in a preterm neonate.